Memory-Like NK Cells: Remembering a Previous Activation by Cytokines and NK Cell Receptors - Pahl, Jens H. W.; Cerwenka, Adelheid; Ni, Jing (Frontiers in Immunology, 2018)
Natural Killer (NK) cells are cytotoxic innate lymphoid cells serving at the front line against infection and cancer. In inflammatory microenvironments, multiple soluble and contact-dependent signals modulate NK cell responsiveness. Besides their innate cytotoxic and immunostimulatory activity, it has been uncovered in recent years that NK cells constitute an enormous heterogeneous and versatile cell subset. Persistent memory-like NK populations that mount a robust recall response were reported during viral infection, contact hypersensitivity reactions, and after stimulation by pro-inflammatory cytokines or activating receptor pathways. In this review, we highlight recent findings on the generation, functionality, and clinical applicability of cytokine-induced and antibody-induced memory-like NK cells and describe common features in comparison to other recent concepts of memory NK cells. Understanding of these features will facilitate the conception and design of novel NK cell-based immunotherapies.